ПОЗИКОВА ПОЛІТИКА СЕЛЯНСЬКОГО БАНКУ НА ПІВДНІ УКРАЇНИ (Zaporizhzhia Historical Review, 2021)
The article analyzes the Peasantís Bank activity in Southern Ukraine, reviews research by historians of the history and directions of the Bankís work, the consequences of the loan policy of the Bank. The statistic calculations about peasantsí (clients of the Peasantís Bank) personal and real property are presented in it.